Enhancing EFL speaking in rural settings : challenges and opportunities for material developers (2018)
Eng: There are several reasons why english language teachers may embark on the endeavor to develop teaching and learning materials for the EFL population in rural schools.  This book presents some of those reasons by means of illustrating the fluctuating challenges and opooortunities while developing contextualized materials to enhance the speaking skill in rural settings.  In the same way, it displays some theotetical constructs and results which emerged from an action research study that sought to analyze what the design and implementation of workshops, based on rural students' needs, revealed abut their speaking skill development.  Consequently, the authors suggest that using contextualized material increases students' possibilities to overcome personal weaknesses which may prevent them from communicating in the target language and manage some factors affecting second language learning.  Then, they conclude that developing contextualized material becomes meaningful and useful for the teaching and learning processes when it integrates humanizing perspectives.